ANIRIDIA: A RARE MANIFESTATION OF CONGENITAL RUBELLA SYNDROME - Hussain, Ali Shabbir; Ali, Syed Rehan; Mohammad, Nadia; Ali, Nabiha; Ahmad, Shakeel; Ahmad, Tauseef (Journal of Ayub Medical College Abbottabad, 2018)
A foetus affected by a congenital rubella infection can develop congenital rubella syndrome (CRS). Aniridia is the absence of iris, rarely been described in literature in association with CRS, can easily be overlooked, leading to complications e.g. glaucoma and blindness later in life. We report a case of a neonate with CRS and aniridia presenting at a tertiary care hospital. Keywords: Aniridia; Congenital; Rubella; Syndrome; Iris; Hypoplasia